2008
DOI: 10.1111/j.1444-2906.2007.01492.x
|View full text |Cite
|
Sign up to set email alerts
|

Fishing strategy choices of purse seines in the Mediterranean: implications for management

Abstract: An observer's sampling scheme, that employed fisheries scientists onboard fleet vessels was used to examine temporal fishing tactics and strategies affecting catches of the purse seine fishery in the Mediterranean. The month, water depth and the fishers' behavior were found to have an effect on total and Trachurus spp. retained catches, with fishers' behavior explaining the largest percentage of the data variation. The distance of the fishing ground from port and the market price modulated both the retained ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 26 publications
1
20
0
1
Order By: Relevance
“…Purse seining with light is among the most important fishing practices in the Mediterranean Sea being able to harvest large quantities of shoaling fish such as sardinella, sardine, anchovy, mugilids, horse mackerel, sand smelt, etc. (Papaconstantinou and Farrugio 2000, El-Haweet 2001, Tsitsika and Maravelias 2008. The typical purse seine practice involves anchoring lamp rafts with their lights turned on for some time in order to attract a fish school.…”
Section: Introductionmentioning
confidence: 99%
“…Purse seining with light is among the most important fishing practices in the Mediterranean Sea being able to harvest large quantities of shoaling fish such as sardinella, sardine, anchovy, mugilids, horse mackerel, sand smelt, etc. (Papaconstantinou and Farrugio 2000, El-Haweet 2001, Tsitsika and Maravelias 2008. The typical purse seine practice involves anchoring lamp rafts with their lights turned on for some time in order to attract a fish school.…”
Section: Introductionmentioning
confidence: 99%
“…Observations made by fisheries scientists onboard confirmed that in the Mediterranean purse-seine fishery, the retained catches were modulated by both market price and distance from port (Tsitsika and Maravelias, 2006;Tsitsika et al, 2007). Furthermore fishers adapted their fishing operations in that way so as to return to port as early as possible and sell their catches at the best price they could ("profit maximisers", Tsitsika and Maravelias, 2008). It is more than likely that the performance of the models could be improved with the inclusion of additional information, not readily available, such as stock size, recruitment fluctuations, fishing ground, skipper age/education, crew etc.…”
Section: Discussionmentioning
confidence: 64%
“…As largest vessels have higher levels of engine power are able to steam in different fishing grounds and thus conduct more fishing operations than the smaller vessels in a given trip (Guyader and Daurès, 2005;Tsitsika and Maravelias, 2008). In a typical Mediterranean purse-seine fishery vessels operate exclusively during night hours i.e., from 20:00 to 05:00.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations